التوزيع الاحتمالي الأمثل لدراسة خسائر حوادث السيارات وقياس الخطر دراسة تطبيقية على الشركة الوطنية وشركة المشرق العربي للتامين - عكروش محمد (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The concerned authorities shall take all necessary measures to reduce the number of traffic accidents, such as expanding roads, bridges, and tunnels, and the integrating traffic safety measures on the networks of these roads to reduce traffic accidents. However, the number of these accidents remains high, and is one of the leading causes of death, and disabilities, and material losses, Where the frequency of the accidents occurred during the period covered was / / and the average loss resulting from one accident, was / /SP, Here are the most significant findings of the research: -The probability distribution of the total losses was determined by the probability distribution of the number of accidents and the probability distribution of the loss values ​​resulting from the accident investigation. -The expected value for the total loss was /3024.856953/ and the coefficient of variation was /1957234294.502638/ SP. - There is a difference between the expected value of the total losses and the premium paid to the Syrian Federation of Insurance Companies. - The risk value based on the average of the total loss was 1.22% of the average loss size. تعمل الجهات المعنية على اتخاذ كافة الاجراءات والتدابير اللازمة لتخفيض عدد الحوادث المرورية, كشق الطرقات وتوسيعها وإقامة الجسور والأنفاق, ونشر وسائل السلامة المرورية على شبكات هذه الطرق لتخفيف الحوادث المرورية, الا انها تبقى ذات معدلات مرتفعة, وتعد من اكثر الاسباب المؤدية لحدوث الوفيات والاعاقات والخسائر المادية, حيث بلغ معدل تكرار الحادث خلال الفترة المدروسة/ /, كما بلغ متوسط الخسارة الناجمة عن الحادث الواحد ما مقداره/ / ليرة سورية, ويمكن ان نبين اهم النتائج التي توصل اليها البحث بالآتي: - تم تحديد التوزيع الاحتمالي للخسارات الكلية من خلال التوزيع الاحتمالي لعدد الحوادث والتوزيع الاحتمالي لقيم الخسائر الناجمة عن تحقق حوادث السيارات. - بلغ التوقع الرياضي للخسارة الكلية/3024.856953/ ليرة سورية وبلغ تباينها/1957234294.502638/ ل.س. - يوجد فرق بين التوقع الرياضي للخسارات الكلية وبين قسط التامين المدفوع الى الاتحاد السوري لشركات التامين. - بلغت قيمة الخطر بالاعتماد على متوسط مجموع الخسائر 1.22% من قيمة متوسط حجم الخسارة.